EDUCATIONAL COMMUNICATION MESSAGES BETWEEN TEACHERS AND STUDENTS AT SMPN 1 MARGAHAYU, BANDUNG REGENCY - Nida Yasmin; Nofha Rina (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze educational communication messages between teachers and students at SMPN 1 Margahayu, focusing on three main aspects: conveying positive expectations, communicating learning goals and outcomes, and providing feedback. Ineffective communication often leads to low student participation, lack of clarity of instruction, and decreased learning motivation. Using a qualitative approach and phenomenological method, this study explores the experiences of teachers and students in classroom learning interactions. The results show that teachers convey positive expectations through a fair approach, equitable discussion space, and personal interactions that motivate students. Learning objectives are clearly conveyed from the beginning, helping students understand the direction of learning. Feedback is given concretely, timely and according to students' needs. Teachers also reflect on students' understanding and adjust teaching strategies accordingly. These findings confirm the importance of educational communication that not only conveys information, but also builds emotional connections and encourages active participation. Therefore, strengthening teachers' communication skills is a key factor in creating an inclusive, dialogic and meaningful learning environment.